Child/Revenge Pornography in the Republic of Mauritius: Extent, Challenges, and Potential Approaches for Prevention, Deterrence, and Mitigation. - Fulena, Viraj; Chittoo, Hemant B. (APPS Publications, 2023)
ABSTRACT The phenomenon of Child/Revenge Pornography in the Republic of Mauritius is a sensitive and controversial one. Many may prefer to keep it as a taboo subject. The figures of the extent of the phenomenon are, however, appalling. The most recent figures available from official sources show 1,835,064 attempts in the period 2011 to 2021 to access Child Sexual Abuse sites and 110,026 Mauritian IP addresses having to do with Child Sexual Abuse that have been blocked by ICTA in the same 10-year period. It will not be exaggerated to infer that the situation of ‘moeurs’ in the Republic of Mauritius is deteriorating. Objective – The Government of Mauritius has been reasonably proactive and kept with its tradition of honouring its international obligations all by enacting appropriate laws, like the Children’s Act 2020 and the Cybersecurity and Cybercrime Act 2021 to ensure the problem does not spill out of control. These laws provide a legal framework for addressing various forms of child exploitation and cybercrimes, including child and revenge pornography. They empower law enforcement agencies to investigate and prosecute those involved in these activities. However, the phenomenon is one whereby any single new case is a case ‘de trop’ for the self-respect of a society, for the image and health of society, for the psychological security of victims and has the risk of giving give rise to public outcries. Stricter laws to deter and punish perpetrators, while always welcome, do not reflect a healthily educated and mature society, ethically compliant in terms of desirable behaviour of the great majority of its citizens. Methodology – In order to ensure the robustness of findings and recommendations that emerge, An assessment of the situation based on the review has been done through a semi-structured questionnaire, one to one interview, and a consultative workshop with stakeholders. Findings – This paper has revealed the realistic hard and soft, short, medium and long-term solutions to attack the problem at its root cause. Novelty – Wide consultation via literature review, one-to-one interviews, focus groups of stakeholders and member of Government and Non-Government Organizations, the media, academics, and opinion leaders, among others, do reveal a common understanding of the phenomenon, its extent, its root causes, the legal and institutional framework to combat the phenomenon, their adequacy and effectiveness, and further solutions that can be envisaged for a better Mauritius for our present and future generations. Keywords: pornography; assesment; semi-structured questionnaire; child sexual abuse